Pembentukan Generasi Qur’ani dengan Akhlāq al-Karīmah di Pondok Pesantren Al-Haris Makassar - M. Amirullah; Ronny Mahmuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Real Work Lecture (KKN) STIBA Makassar aims to take a role in helping the government of Tamalate Subdistrict, Makassar City, South Sulawesi Province, in realizing the mission of mental and spiritual development between religious communities by carrying out obligations and “Tri Dharma Perguruan Tinggi” on the pillars of community service. This program begins with the method of analyzing the problems and needs of the community using SOAR analysis techniques. The results of the analysis established the program in the form of stimulation of akhlāq al-karīmah in the form of activities of Daurah Ilmiyah, Taḥsīn and Taḥfīẓ Qur'an, Watch Islamic Films, Lecture Competitions, and Devotional Work. Sharing the variety of activities carried out gives results in the form of increased spirit of learning and akhlāq al-karīmah from the students of Pesantren Al Haris.